THE POTENTIAL IMPLEMENTATION OF DIGITAL MARKETING WITH SOCIAL INFLUENCERS IN HOSPITALS: A LITERATURE STUDY - Gunawan, Sri Rahmah; Dewanto, Aryo (Journal of Community Health and Preventive Medicine, 2025)
Digital media provides opportunities to expand into new markets, offer services and implement new online communication techniques. Patients as service consumers increasingly use the internet or other digital technologies to get the right information. There is not much research on the opportunities of using social influencers as a hospital marketing strategy. Therefore, this research aims to find out the opportunities that can be used by hospitals in the use of social media as a marketing tool with social influencers. The research method used is a literature study. The literature search in this literature review uses databases in the form of Google Scholar, Emerald, Elsevier, and Proquests. From the search results, articles are selected and grouped based on relevance to digital marketing topics and social influencers. A total of 10 articles were reviewed to obtain results in accordance with the purpose of the literature review. The results of the research show that digital technology marketing with social media influencers can provide good opportunities for hospitals. Social media influencers can create interesting content for hospitals so as to build mutually beneficial relationships with influencers whose characters are in accordance with the brand image or hospital. The results of this research can be used by hospital management as a basis for the development of social media with the help of social influencers as a means for hospital marketing.